1997
DOI: 10.1002/(sici)1096-8628(19971031)72:3<307::aid-ajmg11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Tetraphocomelia and bilateral cleft lip in a historical case of Roberts syndrome [Virchow, 1898]

Abstract: We discuss an unlabelled specimen of tetraphocomelia and bilaterally cleft lip from the former Virchow Museum of our Medical School. Identity of the subject with a case of what was later termed "Roberts syndrome" published by Rudolf Virchow in 1898 is demonstrated. Rediscovery of this important historical case is gratifying, since almost 95% of the specimens of Virchow's collection were lost during World War II. We have restudied Virchow's case. Recent CT scan images of the fetus are presented. We review data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In both cases, however, the feet contained five metatarsals and five digits. This is significant because even in severe RBS, in which the long bones are absent, rather normally shaped feet are attached to the pelvis, as in Virchow's 1898 case (Urban et al 1997) and the proband of our family 5. Minor abnormalities, such as short halluces and wide spaces between the first and second toes, may be present.…”
Section: Figurementioning
confidence: 69%
“…In both cases, however, the feet contained five metatarsals and five digits. This is significant because even in severe RBS, in which the long bones are absent, rather normally shaped feet are attached to the pelvis, as in Virchow's 1898 case (Urban et al 1997) and the proband of our family 5. Minor abnormalities, such as short halluces and wide spaces between the first and second toes, may be present.…”
Section: Figurementioning
confidence: 69%
“…85,86 Patients who share features that overlap between thrombocytopeniae absent radius (TAR) syndrome and this disorder have been described (see ''ThrombocytopeniaeAbsent Radius Syndrome,'' below). 87 Cytogenetic studies of some patients have shown consistent chromosomal abnormalities, including premature centromere separation and centromere splitting and puffing. 88,89 No genetic locus defect has yet been identified for this syndrome.…”
Section: Adams-oliver Syndromementioning
confidence: 99%
“…Geoffroy Saint Hillaire's description of “seal limb” syndrome in 1838 (“hands or feet of unusual size and commonly even completely normal, which, supported by excessively short limbs usually emerge directly from the shoulders or hips”) also seems to anticipate Roberts [Grundy et al, 1988]. A fetus described by Virchow in 1898 has recently been interpreted as Roberts syndrome after reexamination of the specimen [Urban et al, 1997], and another case has been identified among the specimens in the teratological collection of the Museum Vrolik in Amsterdam [Oostra et al, 1998]. A diagnosis of Roberts syndrome has also been proposed in a case reported in Germany in 1737 [Bates, 2001b].…”
Section: Roberts Syndrome Before Robertsmentioning
confidence: 99%